PROBLEMS AND SHORTCOMINGS IN FINANCING COST ESTIMATES AND STAFFING TABLES (Global Economic Review: Journal of Economics, Policy, and Business Development, 2026)
This article analyzes the existing problems and shortcomings in the process of financing expenditure estimates and staffing tables. It examines issues such as the lack of accuracy in planning, imbalances in the allocation of financial resources, incomplete implementation of regulatory and legal documents in practice, and weaknesses in financial control mechanisms. In addition, the article proposes recommendations aimed at eliminating identified problems and improving the efficiency of the financing system.